Energy Conservation Assessing : A Case Study of The Natural History Museum of Khon Kaen University - Piriyasatta, Pornsawat (Journal of Building Energy & Environment, 2021)
The objective of this research was to assess the natural history museum of Khon Kaen University, in terms of energy conservation and in accordance with the criteria of the Ministerial Regulations and Announcements of the Ministry of Energy. This was accomplished by exploring and collecting the information about the building, including the building’s physical data, building materials and building systems. The data was calculated and analyzed using the BEC v.1.0.6 program. A building’s energy conservation can be assessed via two options. The assessment for option 1 revealed that the building’s envelope system had shown a total OTTV value of 52.45 watts per square meter and a total RTTV value of 3.68 watts per square meter. According to the criteria, the total OTTV value must be less than 50 watts per square meter. Therefore, the building’s envelope system had failed the criteria. The building systems, which had met the criteria, consisted of the lighting system with the maximum power density of 13.754 watts per square meter and the air conditioning system with COP values of 3.236 and 3.227, the results of the assessment for option 1 had failed to meet the criteria. In contrast, the assessment for option 2 found that the whole building energy consumption had been equal to 353,978.46 kilowatt-hour per year, which was less than the reference building. The results of the assessment for option 2had met the criteria. An improvement, which could reduce the whole building energy consumption, was determined to be the use of solar cells, which could generate 69,921.07 kilowatt-hour per year of electrical energy. This would allow for a savings 262,554 baht in electricity costs per year with a payback period of 16.79 years.